Polyphasic Evaluation Of Periphytic Freshwater Cyanobacteria In Tukun River, Penang National Park - Azizan, Asmimie Asmawarnie (2017)
Most algae studies in Malaysia have focused on phytoplankton in lakes. Despite the occurrence of numerous streams and rivers in Malaysia, algae community in the lotic ecosystems remained largely unknown. In this study, macroscopic cyanobacteria collected from 9 sites along Tukun River were examined to identify the diversity of the group from December 2014 to November 2015. To the best of our knowledge, this is the pioneer study on periphytic cyanobacteria conducted in the stream of Penang National Park. To date, 24 morphospecies has been identified including 9 family whereby 10 species were encountered from field and the other 14 remaining were identified in cultures. Crust were the most dominant macroscopic forms with 7 morphospecies, followed by mats (3 morphospecies). Scytonema was the most dominant genus occurring at 8 out of 9 sampling sites. Presence of heterocytous cyanobacteria (S. stuposum or S. hofmanni) in 8 out of 9 sampling sites coincide with the low nitrate value (<074mg/L) recorded throughout the study stream. Chroococcales were dominant in both upper and middle stream. Environmental factor were also included in identification of cyanobacterial diversity along the study sites.